Perspectives of clinical genetics professionals toward genome sequencing and incidental findings: a survey study. (7th December 2012) - Lemke, AA; Bick, D; Dimmock, D; Simpson, P; Veith, R
<x xml:space="preserve">Abstract</x> The introduction of clinical genome‐wide sequencing raises complex issues regarding the management of incidental findings. However, there is a lack of empirical studies assessing views of providers involved in potential disclosure of such findings. In an anonymous survey of 279 clinical genetics professionals, we found that the vast majority of participants agreed that they were interested in knowing about clinically actionable incidental findings in themselves (96%) and their child (99%), and they reported that these types of findings should be disclosed in adult (96%) and minor (98%) patients. Approximately three‐fourths agreed that they were personally interested in knowing about an adult‐onset clinically actionable disease (78%) and a childhood‐onset non‐clinically actionable disease (75%) in their child. A similar percentage of participants (70%) felt that these two types of findings should be disclosed to patients. Forty‐four percent of participants wanted to know about an incidental finding that indicates an adult‐onset non‐clinically actionable condition in themselves and 31% wanted to know about this type of information in their child. Findings from this study revealed participants' views highly dependent on clinical actionability. Further research is needed with a broader population of geneticists to increase generalizability, and with diverse patients to assess their perspectives about results disclosure from clinical sequencing.